2022
DOI: 10.1371/journal.pone.0265138
|View full text |Cite
|
Sign up to set email alerts
|

Daily actual evapotranspiration estimation of different land use types based on SEBAL model in the agro-pastoral ecotone of northwest China

Abstract: Evapotranspiration (ET) plays a crucial role in hydrological and energy cycles, as well as in the assessments of water resources and irrigation demands. On a regional scale, particularly in the agro-pastoral ecotone, clarification of the distribution of surface ET and its influencing factors is critical for the rational use of water resources, restoration of the ecological environment, and protection of ecological water sources. The SEBAL model was used to invert the regional ET based on Landsat8 images in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…SLSTR, referring to the sea and land surface temperature radiometer, is a dual-scan temperature radiometer selected for the ESA Sentinel-3 mission in low Earth orbit as a part of the Copernicus Programme [67]. It provides a full range of applications related to earth observation, the most prominent of which are the sea surface temperature (SST) assessment and land monitoring [68,69]. SLSTR products offer highly accurate global and regional sea and land surface temperatures (SST and LST) for climatological and meteorological applications.…”
Section: Used Data and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…SLSTR, referring to the sea and land surface temperature radiometer, is a dual-scan temperature radiometer selected for the ESA Sentinel-3 mission in low Earth orbit as a part of the Copernicus Programme [67]. It provides a full range of applications related to earth observation, the most prominent of which are the sea surface temperature (SST) assessment and land monitoring [68,69]. SLSTR products offer highly accurate global and regional sea and land surface temperatures (SST and LST) for climatological and meteorological applications.…”
Section: Used Data and Processingmentioning
confidence: 99%
“…Furthermore, Yang et al [69] demonstrated that NDVI patterns are usually consistent with the AET spatial distribution, while [45] demonstrated that the SAR backscatter and NDVI can be used in various physical environmental conditions because they have suitable optical plant properties. The least influential variables were the radar vegetation index (RVI), which measures the randomness of the scattering [110], and the ratio VH/VV, both associated with vegetation conditions.…”
Section: Relative Influences Of the Variables On The Modelmentioning
confidence: 99%
“…Yang et al investigated actual ET in different land uses based on the SEBAL algorithm and landsat 8 images in Ecotone, Northwestern China. The SEBAL algorithm had an appropriate estimation (RMSE = 0.9 mm/day and R 2 = 0.81), which was suitable for research on water resources, but it overestimated ET (Yang et al 2022). In another study, Wei et al evaluated daily ET estimation of rice fields, using the SEBAL algorithm in a subtropical region in Southern China.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms have been applied for various purposes, such as the management of irrigated crops (Souza et al, 2019;Yang et al, 2022), quantification of watershed evaporation (Chao et al, 2021), and determination of agricultural crop ETr (Grosso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%